Spirometric alterations in post-COVID-19 patients treated on an outpatient. Ibarra, January–December 2021 - Paulina Marilú Puedmag Rueda; Pedro René Torres Cabezas; Jorge Luis Anaya González (Medisur)
Foundation: among the best lung function tests is spirometry. In post-COVID-19 patients, this allows us to evaluate the severity of the condition and follow the progression of airflow limitation, to identify obstructive, restrictive and mixed patterns. Objective: to determine the spirometric alterations and their relationship with the severity degree of the post-COVID-19 condition in patients treated on an outpatient. Methods: descriptive, cross-sectional study, which included 40 patients treated on an outpatient in the Ibarra city, from January to December 2021, who underwent spirometry one year after infection to determine the presence of spirometric alterations and its relationship with the severity degree of the COVID-19 condition. Results: one year after infection, moderate (22.5%) and severe (5%) cases presented alterations in spirometry. A mild restrictive type pattern was identified in 17.5%; and moderate in 10.5% of them. Spirometric alterations did not present a statistically significant relationship with the severity of COVID-19 (p>0.05). In isolation, the FEV1/FVC ratio was significantly associated with moderate (p=0.027) and severe (p=0.017) COVID-19. Furthermore, in these same groups an increase in systolic blood pressure was evident during the presentation of their clinical symptoms (p=0.009 and p=0.004, respectively). Conclusions: The restrictive pattern of mild and moderate degree was the fundamental spirometric alteration in post-COVID-19 patients, which was not associated with the severity of the disease.